(untitled) (TAJ: Journal of Teachers Association, 2009)
To evaluate the thyroid hormone levels in pre-eclampsia and normal pregnancy, a study was undertaken among 54 women of age ranged from 18 to 35 years without present or past history of thyroid diseases. Among the study subjects, 32 women were patients of pre-eclampsia, 12 women were in their normal third trimester pregnancy and 10 women were married but nonpregnant (without having hormonal contraceptives at least for 6 months). We have measured serum levels of total and free thyroxine (TT4 & FT4) and total and free triiodothyronine (TT3 & FT3) by using RIA. The mean serum TT4 and TT3 in normal pregnancy were significantly higher compared to that of non-pregnant women when mean FT4 and FT3 were similar in both normal pregnancy and non-pregnant women. In pre-eclampsia, mean serum TT4 and TT3 were significantly higher than that of non-pregnant women but compared to that of normal pregnancy, TT4 was clearly higher but not significant when TT3 was significantly lower. The mean serum FT4 was significantly higher in pre-eclampsia compared to non-pregnant women and not significantly higher compared to normal pregnancy. The mean serum FT3 was similar in both non-pregnant and normal pregnancy but significantly lower in pre-eclampsia compared to normal pregnancy. In pregnancy i.e. in both normal pregnancy and pregnancy with preeclampsia, the increased serum thyroid hormone levels might result from increased stimulatory effect of placental hormones (hCG), increased metabolic demands in pregnancy and mental stress in pregnancy as mentioned by other investigators. Decreased TT3 and FT3 associated with higher TT4 in pre-eclampsia might be due to reduced conversion of T4 to T3 in the liver and kidneys. doi: 10.3329/taj.v20i1.3082 TAJ 2007; 20(1): 06-10